Increased coronary heart disease and stroke hospitalisations from ambient temperatures in Ontario. Issue 8 (3rd November 2017) - Bai, Li; Li, Qiongsi; Wang, Jun; Lavigne, Eric; Gasparrini, Antonio; Copes, Ray; Yagouti, Abderrahmane; Burnett, Richard T; Goldberg, Mark S; Cakmak, Sabit; Chen, Hong
Abstract : Objective: To assess the associations between ambient temperatures and hospitalisations for coronary heart disease (CHD) and stroke. Methods: Our study comprised all residents living in Ontario, Canada, 1996–2013. For each of 14 health regions, we fitted a distributed lag non-linear model to estimate the cold and heat effects on hospitalisations from CHD, acute myocardial infarction (AMI), stroke and ischaemic stroke, respectively. These effects were pooled using a multivariate meta-analysis. We computed attributable hospitalisations for cold and heat, defined as temperatures above and below the optimum temperature (corresponding to the temperature of minimum morbidity) and for moderate and extreme temperatures, defined using cut-offs at the 2.5 th and 97.5 th temperature percentiles. Results: Between 1996 and 2013, we identified 1.4 million hospitalisations from CHD and 355 837 from stroke across Ontario. On cold days with temperature corresponding to the 1 st percentile of temperature distribution, we found a 9% increase in daily hospitalisations for CHD (95% CI 1% to 16%), 29% increase for AMI (95% CI 15% to 45%) and 11% increase for stroke (95% CI 1% to 22%) relative to days with an optimal temperature. High temperatures (the 99 th percentile) also increased CHD hospitalisations by 6% (95% CI 1% to 11%) relative to the optimal temperature. These estimates translate into 2.49% of CHD hospitalisations attributable to cold and 1.20% from heat. Additionally, 1.71% of stroke hospitalisations were attributable to cold. Importantly, moderate temperatures, rather than extreme temperatures, yielded the most of the cardiovascular burdens from temperatures. Conclusions: Ambient temperatures, especially in moderate ranges, may be an important risk factor for cardiovascular-related hospitalisations.